2005
DOI: 10.1103/physrevb.71.081306
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced nonlinear optical response of InP(100) membranes

Abstract: The nonlinear optical response of porous InP͑100͒ membranes was examined and compared to that of bulk crystalline ͑100͒-oriented InP. Measurements of optical rectification and optical second-harmonic generation have been carried out in reflection under excitation by 120 fs, 800 nm Ti:Sapphire laser beam pulses. A significant enhancement in both the radiated terahertz field and second-harmonic radiation from the porous InP͑100͒ surface, relative to the bulk InP͑100͒ surface, was observed. Terahertz field polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 19 publications
2
19
1
Order By: Relevance
“…2 ͑Conversely, an absence of magnetic field dependence and nonsaturation with excitation fluence, as exemplified by GaBiAs, 3 rule out the influence of TC.͒ Porous membranes on ͑100͒ InP surfaces give an enhanced NLO response for both second-harmonic and terahertz generation, related to optical rectification ͑OR͒ rather than to TC effects, and attributed to strong local fields in the porous network. 4 Similar enhancements to the terahertz emission in porous samples relative to the bulk precursors have been observed for ͑111͒ InP. 5 Measurements and modeling on charge carriers in porous InP membranes indicate a lower density and lower mobility but much longer recombination lifetime than for bulk InP, attributed to upward bandbending at the pore surfaces.…”
mentioning
confidence: 54%
“…2 ͑Conversely, an absence of magnetic field dependence and nonsaturation with excitation fluence, as exemplified by GaBiAs, 3 rule out the influence of TC.͒ Porous membranes on ͑100͒ InP surfaces give an enhanced NLO response for both second-harmonic and terahertz generation, related to optical rectification ͑OR͒ rather than to TC effects, and attributed to strong local fields in the porous network. 4 Similar enhancements to the terahertz emission in porous samples relative to the bulk precursors have been observed for ͑111͒ InP. 5 Measurements and modeling on charge carriers in porous InP membranes indicate a lower density and lower mobility but much longer recombination lifetime than for bulk InP, attributed to upward bandbending at the pore surfaces.…”
mentioning
confidence: 54%
“…It has been recently reported that the THz emission from InP irradiated with 800nm femtosecond laser pulses can be enhanced by introducing a porous surface [13], [14] . Moreover, Gregor also reported metal grating on the semiconductor surface can produce THz radiation based on plasma oscillation [15], [16] .…”
Section: Introductionmentioning
confidence: 99%
“…This could be eliminated by placing nonlinear crystal in hollow metallic waveguide structure . The conversion efficiency in optical rectification depends primarily on the material nonlinear coefficient and the phase-matching conditions and various schemes for power enhancement have been reported [Radhanpura et al, 2010;Bugay & Sazonov, 2010;He et al, 2008;Reid et al, 2008].…”
Section: Optical Rectification Based Emittersmentioning
confidence: 99%